Modos de representar el envejecimiento y la ancianidad en el cine de Almodóvar - Dr. Agustín GÓMEZ GÓMEZ (Fonseca, Journal of Communication, 2023)
Our study starts with an analysis of the elderly characters in the twenty-two films by Pedro Almodóvar. The initial data are revealing. Older people appear in 14 films, with a total of twenty-five older secondary characters, to which we add four scenes with a group of older people as well. Age is not portrayed as a problem in his films, but there are characters in their third and fourth age who present, like his characters of other ages, very marked characteristics.